ACL reconstruction in youth athletes results in an improved rate of return to athletic activity when compared with non-operative treatment: a systematic review of the literature. Issue 2 (27th January 2016) - Fabricant, Peter D; Lakomkin, Nikita; Cruz, Aristides I; Spitzer, Elad; Marx, Robert G
Abstract : Background: Anterior cruciate ligament (ACL) tears are being seen and treated with increasing frequency in youth athletes, with the goal of returning patients to sports activity. This is particularly important for youth athletes, for whom sports provide physical, social and psychological development. Objectives: To perform a systematic review of the orthopaedic surgery literature to investigate for any associations between treatment strategy and return to athletic activity after ACL tear in youth athletes under age 18 years. Data sources: PubMed, EMBASE and Cochrane computerised databases. Study eligibility criteria: Inclusion criteria: (1) <18 years of age, (2) investigation of a relationship between time to treatment and consequent rates of returning to preinjury levels of athletic activity, (3) original research article (eg, not a review, case report or meta-analysis). Exclusion criteria: (1) revision ACL surgery, (2) language other than English, and (3) not a clinically based study. Participants: Youth <18 years old with ACL tears. Interventions: Acute ACL reconstruction, delayed ACL reconstruction, non-operative management. Synthesis methods: Qualitative synthesis. Results: Twenty studies met inclusion and exclusion criteria, of which four evaluated return to play after acute ACL reconstruction (ACLR), five studies evaluated return to play after delayed ACLR, and nine evaluated return to play after ACLR with an unspecified injury-to-surgery time interval. Two studies investigated return to play in a non-operative cohort. Of the 18 surgical studies, 14 employed a soft tissue transphyseal reconstruction. Rates of return to play were 78–100% after acute ACLR, 84–100% after delayed ACLR, 41–100% after ACLR with an indeterminate injury-to-surgery time interval and 6–52% after non-operative treatment of ACL tear. Limitations: Several studies did not provide details about the timing of injury-to-surgery, and study heterogeneity precluded combining results in quantitative meta-analysis. Furthermore, the amount of time to full postinjury recovery remains largely unstudied. Conclusions and implications of key findings: Based on available literature, there appears to be an improved rate of return to athletic activity after ACLR when compared with non-operative treatment. Future research should directly focus on time to return to sports activity, while taking into account the unique aspects of ACL reconstruction and non-operative management in youth athletes. This is of particular importance in children and adolescents given the physical, social and psychological development that occurs with sports participation. Trial registration number: CRD42015027536.